Pulse Wave Analysis in Obese Children with and without Metabolic Syndrome - Cemaliye Başaran; Gökçen Erfidan; Özgür Özdemir-Şimşek; Seçil Arslansoyu-Çamlar; Demet Alaygut; Fatma Mutlubaş; Cem Karadeniz; Bumin Nuri Dündar; Belde Kasap-Demir (JCRPE, 2023)
INTRODUCTION: To compare pulse wave analysis (PWA) of obese children with and without metabolic syndrome (MS) with healthy, non-obese children and to evaluate the association between PWA findings and additional risk factors present in children with MS and obesity. METHODS: From the obese patients examined between June 2019 and June 2021, 41 patients with MS, 36 obese patients without MS, and 34 healthy non-obese children of similar age and gender were evaluated retrospectively. Anthropometric measurements, biochemical evaluation, 24-hour ambulatory blood pressure (BP) measurement (ABPM), left ventricular mass index (LVMI) and PWA measurements were compared. RESULTS: When the three groups were compared, weight standard deviation score (SDS), height SDS and body mass index SDS were all significantly higher in the MS group (p<0.05). The following measurements were significantly higher in both MS and non-MS obese patients compared to the control group: from ABPM measures, the systolic and mean arterial pressure BP SDSs load; from PWA, the night central systolic BP, 24-hour, day and night pulse pressure values and 24-hour, day and night pulse wave velocity (PWV) rates; and from cardiac evaluations, the LVMI and relative wall thickness measurements (all p<0.05). Furthermore, the 24-hour and daytime central systolic (cSBP) and diastolic BP (cDBP) values were significantly different between the three groups, being the highest in the MS group (p<0.05). DISCUSSION AND CONCLUSION: Obesity causes higher office, ambulatory and central BP, PWV and LVMI. However our results suggest that additional risk factors associated with MS do not contribute to these parameters, except for 24-hour and daytime cSBP and cDBP values.